(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Neonatal Asphyxia is one of the risk factors for hearing loss in children. Neonatal Asphyxia causes cochlear damage due to lack of oxygenation and tissue perfusion which can lead to cell death. Objective: Determining the risk of Neonatal Asphyxia for the occurrence of sensorineural hearing loss in children. Methods: A case control study was done between July to September 2020. Children with sensorineural hearing loss are on study group and the control group is children with normal hearing. Participants were measured for previous labor history based on medical records that confirmed asphyxia. Participants were also examined for DPOAE and ABR / BERA. The measurement results were analyzed using the Chi-Square test, which was significant if p <0.05. Results: Most participants aged 2-3 years experienced hearing loss (65.96%) and normal (68.08%; p = 0.835). Participants of sensorineural hearing loss with Neonatal Asphyxia (57.4%) were more than non- Neonatal Asphyxia (42.6%; OR = 1.82; 95% CI 0.81 - 4.13; p = 0.149). Conclusion: Neonatal Asphyxia increases the risk of sensorineural hearing loss by 1.82 times compared to children without Neonatal Asphyxia.